AflaILVB/G/I and AflaILVD are involved in mycelial production, aflatoxin biosynthesis, and fungal virulence in Aspergillus flavus - Zhao, Yarong; Huang, Chulan; Zeng, Rui; Chen, Peirong; Xu, Kaihang; Huang, Xiaomei; Wang, Xu (Frontiers in Cellular and Infection Microbiology, 2024)
Aflatoxins (AFs) are produced by fungi such as Aspergillus flavus and A. parasiticus and are one of the most toxic mycotoxins found in agricultural products and food. Aflatoxin contamination, which requires the control of A. flavus, remains problematic because of the lack of effective strategies and the exploration of new compounds that can inhibit A. flavus growth and mycotoxin production is urgently required to alleviate potential deleterious effects. Acetohydroxy acid synthase (AHAS) and dihydroxy acid dehydratase are important enzymes in the biosynthetic pathways of branched-chain amino acids (BCAAs), including isoleucine, leucine, and valine. Enzymes involved in BCAA biosynthesis are present in bacteria, plants, and fungi, but not in mammals, and are therefore, attractive targets for antimicrobial and herbicide development. In this study, we characterized AflaILVB/G/I and AflaILVD, which encode the catalytic and regulatory subunits of AHAS and dihydroxy acid dehydratase, from the pathogenic fungus Aspergillus flavus. The AflaILVB/G/I and AflaILVD deletion mutant grew slower and produced smaller colonies than the wild-type strain when grown on glucose minimal medium, potato dextrose agar, and yeast extract medium for three days at 28°C, and disruption of AflaILVB/G/I caused a significant reduction in conidia production when grown on all kinds of media. Cellular stress assays determined that all strains were sensitive to H2O2. Importantly, the pathogenicity and aflatoxin production were affected when AflaILVB/G/I and AflaILVD were knocked out, particularly AflaILVB/G/I. A series of genes that encoded enzymes involved in aflatoxin synthesis were downregulated, meaning that the knockout of AflaILVB/G/I influenced aflatoxin synthesis in A. flavus strain WT. Collectively, our results demonstrate the potential value of antifungals targeting AflaILVB/G/I in A. flavus.